Elevated ST2 levels are associated with antibody‐mediated rejection in heart transplant recipients. Issue 9 (26th July 2018) - Grupper, Avishay; AbouEzzeddine, Omar F.; Maleszewski, Joseph J.; Grupper, Ayelet; Geske, Jennifer R.; Kremers, Walter K.; Kushwaha, Sudhir S.; Pereira, Naveen L.
Abstract: Soluble ST2 (sST2) is a novel biomarker of inflammation and fibrosis. Elevated sST2 levels (≥35 ng/mL) are associated with worse outcomes in patients with heart failure (HF). There are sparse data regarding the significance of sST2 levels after heart transplantation (HTx). The study aims were to evaluate trends in soluble ST2 levels after the resolution of HF status with HTx and association between post‐HTx sST2 levels and outcomes. Plasma sST2 levels were measured at baseline (median [IQR] of 118 days pre‐HTx) and 12 months post‐HTx in 62 subjects who were stratified into two groups by post‐HTx sST2 levels < or ≥35 ng/mL: "Group 1" or "Group 2, " respectively. Plasma sST2 levels were elevated in 58% of patients pre‐HTx and in 50% of patients post‐HTx. There was no association between elevated sST2 levels before and after HTx, and no significant differences in baseline characteristics between Group 1 and Group 2 patients. Group 2 as compared to Group 1 HTx recipients had significantly higher incidence of antibody‐mediated rejection (AMR) for the entire post‐transplant follow‐up period (32% vs 4%, P = 0.006). There was no association between post‐HTx sST2 level status and other post‐HTx outcomes including survival. In conclusion, elevated plasma sST2 levels after HTx are associated with increased risk for AMR.